The prospective associations of 24-hour movement behaviors and domain-specific activities with executive function and academic achievement among school-aged children in Singapore - Padmapriya, Natarajan; Bernard, Jonathan Y.; Tan, Sarah Yi Xuan; Chu, Anne H. Y.; Goh, Claire Marie Jie Lin; Tan, Shuen Lin; Shek, Lynette P.; Chong, Yap Seng; Tan, Kok Hian; Chan, Shiao-Yng; Yap, Fabian; Godfrey, Keith M.; et al. (Frontiers in Public Health, 2024)
Background Physical activity (PA), sedentary behavior (SB), and sleep are collectively referred to as 24-h movement behaviors, which may be linked to cognitive development in children. However, most of the evidence was based on cross-sectional studies and/or solely relied on parent-reported information on children’s behaviors, and it remains uncertain whether all domains/contexts of PA and SB are similarly associated with executive function and academic achievement. Objective We investigated the prospective associations of accelerometer-measured 24 h-movement behaviors and domain-specific PA and SB with executive function and academic achievement among school-aged children in Singapore. Methods The Growing Up in Singapore Toward healthy Outcomes (GUSTO) cohort used a wrist-worn accelerometer (Actigraph-GT3x+) to measure 24 h-movement behaviors data at ages 5.5 and 8 years. Executive function and academic achievement were assessed using NEuroPSYchology (NEPSY) and Wechsler Individual Achievement Tests at ages 8.5 and 9-years, respectively. Compositional data analyses were conducted to explore the associations of 24 h-movement behavior with outcomes, and multiple linear regression models to examine the associations of domain-specific PA and SB with outcomes (n = 432). Results Among 432 children whose parents agreed to cognitive assessments (47% girls and 58% Chinese), the composition of 24 h-movement behaviors at ages 5.5 and 8 years was not associated with executive function and academic achievement. However, higher moderate-to-vigorous PA (MVPA) relative to remaining movement behaviors at age 5.5 years was associated with lower academic achievement [Mean difference (95% confidence interval): −0.367 (−0.726, −0.009) z-score], and reallocating MVPA time to sleep showed higher academic achievement scores [30 min from MVPA to sleep: 0.214 (0.023, 0.404) z-score]. Certain domains of PA and SB, notably organized PA/sports, outdoor play, and reading books were favorably associated with outcomes of interest, while indoor play and screen-viewing were unfavorably associated. Conclusion The associations between movement behaviors and cognitive outcomes are multifaceted, influenced by specific domains of PA and SB. This study underscores the importance of participation in organized PA/sports, outdoor active play, and reading books, while ensuring adequate sleep and limiting screen viewing, to enhance cognitive outcomes. These findings underscore the need for further research into time-use trade-offs. Such studies could have major implications for revising current guidelines or strategies aimed at promoting healthier 24 h-movement behaviors in children. Study registration https://clinicaltrials.gov/, NCT01174875.